Analisa fatigue life konstruksi geladak pada kapal Landing Craft Tank menggunakan metode elemen hingga - Alamsyah Alamsyah; Merlistyo Driantama Arwan; Amalia Ika Wulandari (TURBO [Tulisan Riset Berbasis Online], 2021)
The Landing Craft Tank ship is the usual vessels used to transport massive vehicles like excavator, bulldozer, heavy cargo and other heavy equipment indispensable for construction work. There are heavy equipment decks on the LCT vessels that are use to hold or support the cargo above it. The purpose of this study was to determine the stress value in the deck construction that has been modeled before with a plate thickness variation of 80%, 90% and 100% which is then followed by finding the value of fatigue life in the deck construction. The method used in the analysis this time is the finite element method which models the construction deck of LCT vessels assisted by finite element based applications. From the results of the study it was found that the stress on the deck construction of LCT vessels with plate thickness 100% was 99.513 MPa, plate thickness 90% was 104.72 MPa and at plate thickness 80% was 105.19 MPa. While the value of fatigue life with a deck plate thickness of 100% is 26.84 years with a number of cycles of 1006700 times, deck plate thickness of  90% is 16.22  years with a number of cycles 129000 times and deck plate thickness of 80% is 15.91 years with a number of cycles 125000.Keywords: Landing Craft Tank, finite element, fatigue life.